Physical models of the larynx source - KACPROWSKI, Janusz (Archives of Acoustics, 1977)
The development of objective acoustic methods in the medical diagnostics of several speech disorders and the resulting clinical applications in laryngology and phoniatry call for a versatile physical model of the human larynx source. Such a model should simulate the physiological structure and the characteristics of the natural, i.e. biological laryngeal system from both the phenomenological and the quantitative points of view. In the present paper the performance and the general characteristics of the human larynx source are briefly described and its acoustic parameters are defined. Special attention is paid to the physical meaning of these parameters and to the parallels which exist between them and the anatomical structure of the biological system. On the basis of a few rationally motivated simplifying assumptions the mechanical model of the human larynx source and its equivalent electrical analogue circuit are described and discussed. Special attention is paid to the two-mass model which is very convenient for diagnostic purposes. The physical interpretation of the model’s acoustic parameters is given and its mathematical description is formulated, the latter being expressed in the form of two sets of differential equations, describing air-flow and mass-movement, respectively. Finally, the convenience and the usefulness of the model in application to laryngological and phoniatric diagnostics of larynx disorders is briefly discussed and validated.